2011
DOI: 10.1073/pnas.1016445108
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellothalamocortical pathway abnormalities in torsinA DYT1 knock-in mice

Abstract: The factors that determine symptom penetrance in inherited disease are poorly understood. Increasingly, magnetic resonance diffusion tensor imaging (DTI) and PET are used to separate alterations in brain structure and function that are linked to disease symptomatology from those linked to gene carrier status. One example is DYT1 dystonia, a dominantly inherited movement disorder characterized by sustained muscle contractions, postures, and/or involuntary movements. This form of dystonia is caused by a 3-bp del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
112
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 113 publications
(124 citation statements)
references
References 40 publications
12
112
0
Order By: Relevance
“…Similar to the imaging studies in patients, abnormal cerebellar function is observed in genetic mouse and rat models of dystonia (LeDoux and Lorden, 2002;Chen et al, 2009;Zhang et al, 2011). Indeed, an increase in metabolic activity in the cerebellum is observed in mouse models of DYT1 dystonia (Ulug et al, 2011;Zhao et al, 2011), similar to imaging studies in DYT1 patients. Furthermore, in normal mice, generalized dystonia is induced by delivery of the excitatory nonselective glutamate receptor agonist kainic acid to the midline cerebellum (Pizoli et al, 2002).…”
Section: Introductionsupporting
confidence: 70%
“…Similar to the imaging studies in patients, abnormal cerebellar function is observed in genetic mouse and rat models of dystonia (LeDoux and Lorden, 2002;Chen et al, 2009;Zhang et al, 2011). Indeed, an increase in metabolic activity in the cerebellum is observed in mouse models of DYT1 dystonia (Ulug et al, 2011;Zhao et al, 2011), similar to imaging studies in DYT1 patients. Furthermore, in normal mice, generalized dystonia is induced by delivery of the excitatory nonselective glutamate receptor agonist kainic acid to the midline cerebellum (Pizoli et al, 2002).…”
Section: Introductionsupporting
confidence: 70%
“…61,81 Studies in patients with clinically manifesting and non-manifesting DYT1 and DYT6 dystonia using diffusionbased tractography 82 showed reduced connectivity of the cerebellum with the thalamus, suggesting that disruption of cerebellar outflow could be an important factor affecting the occurrence of motor symptoms. A very similar pattern of changes in the cerebellar pathway was reported in DYT1 mutant mice with the torsin1A gene mutation, 83 although the relevance of this model to dystonia is debated. Whether these findings are specific to DYT1 and DYT6 dystonia or are also present in sporadic cases is unknown.…”
Section: Dystoniamentioning
confidence: 64%
“…Several mechanisms may underlie these patterns of vulnerability. The exclusive occurrence of molecular and neurodegenerative changes during the first several postnatal weeks suggests that processes highly active during CNS maturation may malities in dystonia (57), including in DYT1 dystonia (31). We sought but were unable to locate postmortem tissue of sufficient quantity or quality to carefully examine for the presence of neurodegeneration in DYT1 dystonia.…”
Section: Discussionmentioning
confidence: 99%